Teacher Selection Analysis at Pangkalpinang Baptist School Using SAW Method - Fitriyani Fitriyani; Devi Irawan; Ari Amir Alkodri; Yuyi Andrika; Melati Suci Mayasari; Chandra Kirana (ISB Atma Luhur, 2026)
Selecting competent teachers plays a vital role in enhancing the quality of education at Pangkalpinang Baptist School. However, the use of subjective judgment in the recruitment process often leads to less effective decision-making. Therefore, this research aims to examine the teacher selection mechanism by applying the Simple Additive Weighting (SAW) method to strengthen the objectivity and precision of the selection decisions. The SAW approach assesses applicants using three main criteria: interview performance (30%), academic test results (35%), and micro teaching skills (35%).Each criterion receives specific weights according to importance levels, followed by calculations to determine candidates with the highest scores. Research results demonstrate that SAW method implementation provides more systematic and transparent decisions in teacher selection. The study evaluated 10 teacher candidates with Eka Sitompul achieving the highest score of 0.85, followed by Fandi Saputra and Vitta Natalia with 0.825 each. This method enables schools to conduct data-based selection, reducing subjectivity in recruitment processes and ensuring selected teaching staff possess competencies aligned with school requirements.